Selected works of D.T. Suzuki. Volume I, Zen - Suzuki, Daisetz Teitaro, 1870-1966; Jaffe, Richard M., 1954-; Buddhist Society Trust (Oakland, California : University of California Press, 2015)
"Daisetsu Teitaro Suzuki is considered a key figure in the introduction of Buddhism to the non-Asian world. Many in the West encountered Buddhism for the very first time through his writings and teaching, and for nearly a century his work and legacy have contributed to the ongoing religious and cultural interchange between Japan and the rest of the world, particularly the United States and Europe. As an early and influential representative of Zen Buddhism outside of Japan, Suzuki shaped the global conversation about the nature of religious practice for much of the twentieth century. This is the first of a multivolume series gathering the full range of Suzuki's writings. Volume 1 (Zen) presents a collection of Suzuki's classic essays as well as lesser-known but equally influential articles on Zen Buddhist thought and practice. Chinese and Japanese characters, which were originally removed from most post-World War II editions of Suzuki's essays, have been reinstated, and the romanization of Buddhist names and technical terms has been updated uniformly throughout the volume. This collection also contains an in-depth introduction to Suzuki's approach to Zen that places his influence in the context of modern developments in religious thought, practice, and scholarship, making this a useful edition for contemporary scholars and students of Buddhism"--Provided by publisher.
Volume 1. Zen -- Volume 2. Pure Land -- Volume 3. Comparative religion
"Published in association with the Buddhist Soceity Trust"--Title page.
"[Volume 3] Volume editors, Jeff Wilson and Tomoe Moriya."
Includes bibliographical references and index.
AAL
Keywords: Suzuki, Daisetz Teitaro, -- 1870-1966 -- Translations into English; Zen Buddhism